Samoświadomość metakognitywna w kształceniu sprawności pisania na studiach neofilologicznych. Na przykładzie italianistyki Uniwersytetu Wrocławskiego - Grabowska, Monika; Zapłotna, Agata (Neofilolog, 2021)
The paper presents the results of a survey conducted in the academic year 2018/2019 among students of Italian Studies at the University of Wroclaw on metacognitive self-consciousness concerning Italian writing proficiency. The questions concerned the students' practice of written forms of expression in their private lives; the contribution (actual or anticipated) of writing proficiency in their current and future professional career; and the evaluation of the teaching of writing proficiency within the university curriculum of Italian Studies. The study was qualitative and conducted from an emic perspective, involving students in metacognitive reflection. The results of the study indicate limited metacognitive self-consciousness on the part of the students of Italian Studies, who are not, however, devoid of any criticism of the practical Italian language course curriculum.